PROCESOS DE INNOVACIÓN Y APROPIACIÓN TÉCNOLÓGICA EN LAS EMISORAS COMUNITARIAS. UN ESTUDIO SOBRE LA COMETA Y LA ESQUINA RADIO EN COLOMBIA - Villa , María Isabel; Triana, Elluz Tatiana Pinilla; Rueda, Lina María Alvarado (Observatorio Magazine, 2021)
The purpose of this research is to analyze the processes of social appropriation of the Information and Communication Technologies in the community radio stations La Cometa and La Esquina Radio located in Colombia. The qualitative analysis uses the semi-structured interview as a research method. The results of the study show how technology can strengthen the communicative projects of community radios, providing mobility, independence and facilitating their relationship and proximity to their communities of influence.